Sosialisasi Pentingnya Pendidikan Tinggi Menggunakan Board Games di SMK Bhakti Karya Cintakarya, Pangandaran: Socialization of the Importance of Higher Education Using Board Games at SMK Bhakti Karya Cintakarya, Pangandaran - Thirafi, Luthfi; Akbarsyah, Nora (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Higher education is a level of education critical to a country's development. Unfortunately, the gross enrollment rate of higher education (APK) remains very low. Pangandaran Regency has a lower APK than the national APK. This issue was addressed by the existence of PSDKU Unpad in Pangandaran; nonetheless, the APK of the Pangandaran Regency did not immediately increase. Socialization is important to enhance public interest in higher education. Socialization occurred at Bakti Kharya Vocational School in Cinta Karya Village, Pangandaran. Board games are used as a medium to socialize about higher education. The text is dense with information regarding the value of higher education and numerous sorts of higher education. The exercise successfully increased the number of students interested in pursuing higher education from 70% to 96%. To ensure the activity's long-term impact, the team provided participants with a WhatsApp group to discuss information on higher education.